Edukacja ucznia z autyzmem w branżowej szkole specjalnej I stopnia w ujęciu praktycznym = Education of a student with autism in a special and vocational school in a practical approach - Wrycz, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An important life problem for every human being is always work and profession. Choosing the right profession and pro-professional orientation is of great importance for a disabled person, including those with autism. It is an important element shaping the image of a young person`s future, often deciding about a "good start" in adult life. Thanks to the right choice, a participant in the vocational education system receives the opportunity to acquire new and improve previously acquired skills as well as abilities, and is given the possibility to acquire professional competences necessary on the modern labor market. The leading role in preparing students with mild intellectual disabilities as well as autism in Słupsk and neighboring municipalities is played by the UNICEF Special School and Educational Center in Słupsk. In the Stage I Special Vocational School, pupils finishing primary school have the opportunity to study in two fields: catering assistant and hotel service assistant. An increasing group of students of the Vocational School are students with mild.
Keywords: praca; edukacja uczniów z niepełnosprawnością intelektualną w stopniu lekkim i autyzmem (niepełnosprawności łączone); szkoła zawodowa dla uczniów z niepełnosprawnością intelektualną w stopniu lekkim; work; education of students with mild intellectual disabilities and autism (combined disabilities); vocational school for students with mild intellectual disabilities